Biochemical Analysis of Lipid Profiles and Oxidative Stress Markers in Cardiovascular Patients with Type-2 Diabetes. A Cross-Sectional Study in Pakistan - Aaisha Qadir, Salma Kadir, Amina Shahid, Shafi Muhammad Wassan, Ambreen Anjum, Noor-ul-Ain Kashif (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Cardiovascular disease (CVD) continues to be a leading cause of morbidity and mortality in patients with type 2 diabetes mellitus (T2DM) particularly in high disease burden areas such as Pakistan. The progression of diabetic cardiovascular complications has been related to dyslipidemia and oxidative stress. This study investigates the biochemical interplay between lipid profiles and oxidative stress markers in cardiovascular patients with T2DM. Methods: A cross-sectional clinical study was done in n=120 patients with T2DM and established cardiovascular disease. Lipid profiles were measured by standardized enzymatic assays according to the National Cholesterol Education Program (NCEP), and International Federation of Clinical Chemistry (IFCC) guidelines on the same day. The oxidative stress was quantified by measuring the level of malondialdehyde (MDA) and the activities of antioxidant enzymes superoxide dismutase (SOD) and catalase (CAT). Pearson’s correlation analysis was used to find the relationships between lipid parameters and oxidative stress markers. Results: The atherogenic lipid profile included elevated total cholesterol, LDL C, triglycerides, and low HDL C. MDA levels were significantly elevated, and SOD and CAT activities were significantly decreased, suggesting a significant increase in oxidative stress. Correlation analysis showed a positive correlation of LDL C and MDA (r = 0.47, p < 0.001) and an inverse correlation of HDL C and MDA (r = –0.39, p = 0.010) which suggests that dyslipidemia is associated with increased oxidative stress in this high-risk population. Conclusion: T2DM cardiovascular patients have significant dyslipidemia and enhanced oxidative stress, both of which may synergistically aggravate cardiovascular risk. Our findings support the therapeutic strategy of combined lipid abnormalities and oxidative stress treatment to improve cardiovascular outcomes in T2DM patients. Keywords: Type‑2 Diabetes Mellitus, Cardiovascular Disease, Dyslipidemia, Oxidative Stress, Lipid Profile, Malondialdehyde, Antioxidant Enzymes, NCEP, IFCC.